IDENTIFICATION OF THERMOSTABLE LIPASE FROM THERMOPHILIC BACTERIA ISOLATED FROM GEDONG SONGO - Herawati Permana, Anita
Lipase (Triacylglycerol hydrolase, E.C. 3.1.1.3) is an enzyme which is able to hydrolise lipid. Thermostable lipase had been isolated from YTae-13, a thermophilic bacteria isolated from Gedongsongo hot spring. Previous research has analysed YTae-13 as Geobacillus lituanicus BGSCW9A89 based on 16S rRNA analysis. Result from growth curve and enzyme production curve at 55oC and 70oC showed that YTae-13 expressed lipase more than once during its lifetime, that are at exponential phase and stationary phase. Stationary phase lipase was chosen to be isolated. Lipase isolation has been conducted by cultivating YTae-13 in Tween20-CaCl2 media at 55oC and pH 6,5 within 17 hours. The extracellular enzyme was separated from the cell by centrifugation and precipitated with ammonium sulfate followed by dialysis. Two distinct peak of lipase activity was observed, that was saturated 0-20% and 60-80% fractions whose activity was detected as 0,753 and 0,207 unit/mg protein respectively. An activity unit was defined as 1 ?mol product deliberated by enzyme per minute at measurement condition (65oC, pH 8,0). Native-PAGE result showed that these fractions still have some protein bands. These fractions were then subjected to heat-shock treatment to denature non-thermostable enzymes. The specific activity increased to 183,159 unit/mg protein for 0-20% fraction and 14,305 unit/mg protein for 60-80% fraction. These activities were increased by by 661 and 52 times for 0-20% and 60-80% fraction respectively compare to those of crude extract (0,277 unit/mg protein). Result of kinetic measurement of 0-20% fraction was 18 mM for Km and 750 unit/mg protein for Vmax.